Causes of delays in construction projects in Turkey - Kazaz, Aynur; Ulubeyli, Serdar; Tuncbilekli, Nihan Avcioglu (Journal of Civil Engineering and Management, 2012)
In both developing and industrialized countries, deviation from a planned time schedule is one of the most frequently encountered problems in construction investments. Various factors faced with during construction period prevent systematic flow of work, which causes time-based anomalies as a conclusion. Considering the vital importance of the construction industry on the macro-economic structure of a country, it is inevitable to be aware of considerable effect of the timely completion on the allocated project budget. In this study, causes of time extensions in the Turkish construction industry and levels of their importance were examined together. In total, 34 factors affecting project duration were taken into account. A questionnaire survey, including these factors, was then applied to 71 construction companies in Turkey, and the outcomes were evaluated by means of statistical analyses. According to the results, “design and material changes” was found to be the most predominant factor, followed by “delay of payments” and “cash flow problems”. In terms of importance levels of factor groups, financial factors were found to be the first group, while environmental factors were the least effective group. It should be also noted that managerial causes of time extensions are encountered in developed and developing countries, whereas financial causes are experienced in developing countries only.